2021
DOI: 10.3390/diagnostics11112165
|View full text |Cite
|
Sign up to set email alerts
|

Serum Organ-Specific Anti-Heart and Anti-Intercalated Disk Autoantibodies as New Autoimmune Markers of Cardiac Involvement in Systemic Sclerosis: Frequency, Clinical and Prognostic Correlates

Abstract: Background: Heart involvement (HInv) in systemic sclerosis (SSc) may relate to myocarditis and is associated with poor prognosis. Serum anti-heart (AHA) and anti-intercalated disk autoantibodies (AIDA) are organ and disease-specific markers of isolated autoimmune myocarditis. We assessed frequencies, clinical correlates, and prognostic impacts of AHA and AIDA in SSc. Methods: The study included consecutive SSc patients (n = 116, aged 53 ± 13 years, 83.6% females, median disease duration 7 years) with clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Conversely, we found lower CRP levels among patients with biopsy-proven myocarditis, arrhythmic presentation, more advanced NYHA class at presentation and a higher likelihood of AHA positivity. This suggests that in myocarditis autoimmune features are associated with a worse disease course [ 2 , 31 , 32 , 33 ], as recently shown by our group [ 34 ]. A role of innate immunity, i.e., the inflammasome, in the development of myocarditis has been suggested [ 35 ], leading to proposing a role for anti-interleukin-1 treatment.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Conversely, we found lower CRP levels among patients with biopsy-proven myocarditis, arrhythmic presentation, more advanced NYHA class at presentation and a higher likelihood of AHA positivity. This suggests that in myocarditis autoimmune features are associated with a worse disease course [ 2 , 31 , 32 , 33 ], as recently shown by our group [ 34 ]. A role of innate immunity, i.e., the inflammasome, in the development of myocarditis has been suggested [ 35 ], leading to proposing a role for anti-interleukin-1 treatment.…”
Section: Discussionsupporting
confidence: 64%
“…In keeping with the worse outcome in autoimmune myocarditis, in this study and in another recent publication from our group [ 34 ] we found a prognostic role of anti-nuclear autoantibodies. In another recent study on systemic cutaneous sclerosis, we found that serum AHA were associated with cardiac involvement and increased risk of cardiac death [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Organ-and disease-specific serum AHA or anti-intercalated disk autoantibodies (AIDA) suggest isolated autoimmune or immune-mediated myocarditis in the context of SIDs [3,40,41]. The measurement of serum AHA and/or AIDA of IgG class should be utilized to identify patients that can especially benefit from immunosuppression [14].…”
Section: Serum Anti-heart Autoantibodiesmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is a chronic connective tissue disorder characterized by vasculopathy, inflammation/autoimmunity and fibrosis 13 that may affect different organs and at different times during the disease evolution, resulting in heterogeneous clinical scenarios. Cardiac involvement in SSc is frequently referred to as “the silent killer.” In the EUSTAR cohort study from Elhai et al, 4 SSc primary heart involvement (SSc-pHI) was deemed to be the cause of 12% of SSc-related deaths.…”
Section: Introductionmentioning
confidence: 99%